Application of the Ex Aequo Et Bono Principle to the Reconsidered Arbitration Award (Case Study of the Decision of the Indonesian National Arbitration Board (BANI) NUMBER 43032/VI/ARB-BANI/2020) - Irgi Fahreza Chandra; Syofiaty Lubis (Journal of Law, Politic and Humanities, 2024)
In business cooperation agreements, it is important to establish measures to prevent future conflicts. This involves adding a "Dispute Resolution" clause in the agreement, which specifies how to handle conflicts using the application of the ex aequo et bono principle, either through the courts or arbitration. The purpose of the Research is to find out the arbitrators apply the principle of ex aequo et bono in arbitration awards, and the court's authority in handling arbitration award cases that are challenged in court. This research uses an empirical juridical method, which is research that seeks to see the law work in society, By using a case approach and statutory approach which aims to study the implementation of a law or legal rule carried out in legal practice and examine references related to the issue being studied, namely the Decision of the Indonesian National Arbitration Board (Bani) NUMBER 43032/VI/ARB-BANI/2020 jo Medan District Court Decision Number 831/Pdt/G/2021/PN Mdn jo Supreme Court Decision 1371 B/Pdt.sus-Arbt/2022. The results showed that the application of the concept of ex aequo et bono can be done if the parties agree to use this principle but it is carried out carefully by the arbitrator, The authority of the court in examining arbitral awards is limited to the annulment of arbitral awards at the first and appellate levels (Supreme Court), registration of arbitral awards and requests for execution of arbitral awards, However, arbitral awards that have reached the final stage of Appeal (Supreme Court) cannot be sued to the court because it is not the authority of the court to examine the case, this is in accordance with court decision number 326/Pdt.G/2023/PN Mdn.